학령 전 음운장애 아동의 비유창성 특성 - 안진영(Jin Yeong Ahn); 하지완(Ji Wan Ha); 권도하(Do Ha Kwon) (언어치료연구, 2013)
본 연구의 목적은 음운장애 아동의 비유창성 특성을 알아봄으로써, 음운처리 결함과 비유창성의 관련성을 파악하고자 하였다. 이를 위하여 학령 전 음운장애 아동 19명과 일반 아동 19명을 대상으로 P-FA-Ⅱ의 필수 과제를 실시하여 두 집단의 비유창성 점수, 비유창성 유형, 구문 내 비유창성 발생 위치를 비교하였다. 연구결과 첫째, 음운장애 아동이 일반 아동보다 유의하게 더 높은 비유창성 점수를 보였다. 둘째, 음운장애 아동과 일반 아동 간 비유창성의 발생 양상이 유사하였다. 두 집단 모두 삽입의 비율이 가장 높았으며, 연장과 막힘의 비율은 낮았다. 두 집단 간 비율의 차이가 두드러졌던 비유창성 유형은 단어부분반복이었다. 셋째, 두 집단 모두 절의 경계와 절의 내부에 상관없이 비유창성이 발생하였다. 이상의 결과를 종합해보면, 음운처리 결함과 비유창성에 관련성이 있다는 것을 시사한다. The purpose of this study was to investigate the relationship between phonological processing deficit and speech disfluencies through disfluency characteristics of phonological disorders. The subjects were 19 children with phonological disorders (PD group) and 19 typically-developing children (TD group). P-FA-Ⅱ was conducted on each subject and disfluency score, disfluency type, and distribution of disfluencies at syntactic locations was compared. The result are as follows. First, the PD group demonstrated a significantly higher disfluency score than the TD group. Second, disfluency occurrence patterns were similar between the two groups. The interjection rate was the highest in both groups, whereas prolongation and block rate was the lowest in both groups. The part-word repetitions rate showed the most difference between the PD and TD group. Third, speech disfluencies occur regardless of syntactic locations (before clause or within clause) in both groups. These findings suggest that there is a relationship between phonological processing deficit and speech disfluencies. KCI Citation Count: 5